2022
DOI: 10.1038/s41433-022-02325-7
|View full text |Cite
|
Sign up to set email alerts
|

Dual wavelength retinal vessel oximetry – influence of fundus pigmentation

Abstract: Background Clinical methods examining oxygenation parameters in humans have been used in many different care settings, but concerns have been raised regarding their clinical utility when assessing people with darker skin pigmentation. While saturation values can be crucial in emergency medicine, they are equally valuable in assessing disease mechanisms and monitoring change in disease progression. Retinal pigmentation varies across individuals and hence, can impact on retinal oxygen parameters. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…[31] Additionally, saturation values from retinal oximetry vary according to retinal pigmentation. [32] We found associations between the RPS and multiple genetic loci previously associated with skin, hair, and iris colour, suggesting that the RPS reflects the degree of retinal pigmentation. Of the 20 genome-wide significant loci identified by conditional analysis in the discovery GWAS analysis, 17 had previously studied associations with hair, skin or iris pigmentation, including 3 that are known to be associated with oculocutaneous albinism (TYR, OCA2 and TYRP1).…”
Section: Discussionmentioning
confidence: 56%
“…[31] Additionally, saturation values from retinal oximetry vary according to retinal pigmentation. [32] We found associations between the RPS and multiple genetic loci previously associated with skin, hair, and iris colour, suggesting that the RPS reflects the degree of retinal pigmentation. Of the 20 genome-wide significant loci identified by conditional analysis in the discovery GWAS analysis, 17 had previously studied associations with hair, skin or iris pigmentation, including 3 that are known to be associated with oculocutaneous albinism (TYR, OCA2 and TYRP1).…”
Section: Discussionmentioning
confidence: 56%
“…The reduction in oxygen consumption detected by oximetry is a biomarker for retinitis pigmentosa and glaucoma (Stefánsson et al, 2017). Patients with higher levels of pigmentation, including those of African descent, may be at higher risk for oximetry defects and measurement errors, and although a correction for pigment is available (Hammer et al, 2008; Hirsch et al, 2022), its full assimilation and testing across race would significantly improve the reliability of retinal oximetry for clinical applications. Such studies are representative of many latent possibilities for clinical diagnostics; however, this goal remains unattained in part due to uncertainty concerning accuracy and calibration.…”
Section: Discussionmentioning
confidence: 99%
“… 9 More recently, Kirsch et al noted differences in large vessel oxygen saturation measures of both arterioles and venules are related to retinal and iris pigmentation. 11 Studies have also shown differences in oxygen saturation with diseases such as diabetes. From those studies, observed retinal vessel oxygen saturation increases in subjects with diabetes, although the amount of change depends on the severity of the disease.…”
Section: Introductionmentioning
confidence: 99%